Combination of sivelestat and N-acetylcysteine alleviates the inflammatory response and exceeds standard treatment for acetaminophen-induced liver injury. Issue 2 (16th December 2019) - Raevens, Sarah; Van Campenhout, Sanne; Debacker, Pieter-Jan; Lefere, Sander; Verhelst, Xavier; Geerts, Anja; Van Vlierberghe, Hans; Colle, Isabelle; Devisscher, Lindsey
Abstract: Hepatocyte death during acetaminophen (APAP) intoxication elicits a reactive inflammatory response, with hepatic recruitment of neutrophils and monocytes, which further aggravates liver injury. Neutrophil elastase (NE), secreted by activated neutrophils, carries degradative and cytotoxic functions and maintains a proinflammatory state. We investigated NE as a therapeutic target in acetaminophen-induced liver injury (AILI). C57BL/6 mice were administered a toxic dose of APAP, 2 h prior to receiving the NE inhibitor sivelestat, N-acetylcysteine (NAC), or a combination therapy, and were euthanized after 24 and 48 h. Upon APAP overdose, neutrophils and monocytes infiltrate the injured liver, accompanied by increased levels of NE. Combination therapy of NAC and sivelestat significantly limits liver damage, as evidenced by lower serum transaminase levels and less hepatic necrosis compared to mice that received APAP only, and this to a greater extent than NAC monotherapy. Lower hepatic expression of proinflammatory markers was observed in the combination treatment group, and flow cytometry revealed significantly less monocyte influx in livers from mice treated with the combination therapy, compared to untreated mice and mice treated with NAC only. The potential of NE to induce leukocyte migration was confirmed in vitro. Importantly, sivelestat did not impair hepatic repair. In conclusion, combination of NE inhibition with sivelestat and NAC dampens the inflammatory response and reduces liver damage following APAP overdose. This strategy exceeds the standard of care and might represent a novel therapeutic option for AILI.